Separation of Inorganic Anions and Phenolic Compounds Using Tetraethylene Oxide-Bonded Stationary Phases in Capillary Liquid Chromatography - Roza Linda; Mohamad Rafi; Lee Wah Lim; Toyohide Takeuchi (Indonesian Journal of Chemistry, 2019)
Tetraethylene glycol monomethyl ether (TEGMM) and tetraethylene glycol (TEG) modified silica were synthesized and used in capillary liquid chromatography as stationary phases. The stationary phases were prepared by chemically bonding TEGMM or TEG on silica via reaction with 3-glycidyloxypropyltrimethoxysilane. The present stationary phases were successfully used for the separation of several inorganic anions and phenolic compounds. The TEG-modified silica stationary phase had a better selectivity and higher retention for five anions compared to TEGMM-modified silica stationary phase. The repeatability of retention time for the five anions was satisfactory on both stationary phases. By using 2 mM sodium chloride as eluent, the relative standard deviation values were in ranging from 0.68–3.21 and 2.00–2.16% for analytes in the TEG-and TEGMM-bonded stationary phase, respectively. It was found that the TEG-bonded stationary phase had hydrophilic properties due to the presence of the hydroxyl group at the end of the TEG chains.